Begoniayenyeniae (Begoniaceae), a new species from Endau Rompin National Park, Johor, Malaysia - Tan, Joanne Pei-Chih (PhytoKeys, 2018)
Abstract. Begoniayenyeniae is a new species of horticultural value known only from the Endau Rompin National Park, Peninsular Malaysia. It is similar to Begoniarajah with which it had previously been confused in the number of tepals and leaf characters. The new species is compared with three similar species, B.foxworthyi, B.rajah and B.reginula and photographs of all four species and descriptions of B.yenyeniae and B.rajah are provided. Molecular analysis using the ndhF-rpl132 chloroplast marker confirms the four species as distinct. Amongst native species, the three variegated species, B.yenyeniae, B.rajah and B.reginula, are some of the most popular Malaysian begonias in cultivation. Based on its restricted distribution, Begoniayenyeniae, under the IUCN Red List Categories and Criteria, is assessed as Critically Endangered.